Komposisi Plankton Yang Terdapat di Danau Kandis, Desa Salak, Kota Sawahlunto - Dra. NURSYAHRA M.Si, NURSYAHRA (STKIP PGRI Sumatera Barat, 2011)
Research about composition of plankton in Kandis Lake have been the survivaldescriptive method. The result have be composed of plankton in Kandis Lakemuch group to phytoplankton. Phytoplankton those genus were : Lyngbia,Spirulina, Oscillatoria, Merismopedia, Oedogonium, Closterium, Cosmarium,Pediastrum, Desmidium, Cladophora, Coscinodiscus, Trepsinoe, Meloisira,Surirella, Gyrosigma, Navicula, Cymbella, Fragillaria, Synedra and Euglena.Zooplankton those genus were : Moina, Cylops, Diaptomus, Nauplius, Oroperla,Astramoeba, Difflugia, Branchinus, Chephalodella, Filinia, Lepadella, Lycane,Notolcha, Proales, Tetramastix and Testudinella.